비정규직 청년의 근무환경과 건강영향의 요인에 관한 연구 - 최길용(Kilyong Choi); 김호현(Hohyun Kim) (한국콘텐츠학회 논문지, 16(12), 2016)
Objectives: While the proportion of the non-regular workers youth increases in labor market, the differential conditions of temporary employee are increased. Methods: Research objects were 4,322 youth (from 15 to 29) among members of workers who responded to 2014 PSWCI panel report. Statistical analyses were performed using the SAS version 9.4 (SAS Institute Inc., Cary, NC, USA). Data were analyzed using frequency test, t-test, ANOVA and multiple regression. Results: According to results of analysis, youth had differences in youth temporary workers, working conditions, classification of occupation, working period, and health conditions based on work-time conditions. Conclusions: Youth workers, policies on working hours will need to take steps toward reducing working hours and improve a health promoting hierarchy for work environment. 우리나라 비정규직 청소년의 노동 시장이 지속적으로 증가하며, 불안한 요소가 지속적인 환경의 변화로 건강상의 문제로 변하고 있다. 이에 본 연구의 목적은 비정규직의 청년 근로자의 근무환경이 건강문제에 미치는 요인을 파악하고자 하였다. 본 연구에서는 제4차 근로환경조사 자료를 활용하여 청소년 근로자(15세~29세) 4,322명 대상으로 통계 분석하였다. 통계 분석은 SAS 버전 9.4(SAS Institute Inc., Cary, NC, USA)로 이루어 졌으며, t 검정, NOVA 및 다중 회귀 분석을 하였다. 그 결과 개인, 일반 특성 (환경 노동자), 근무 시간, 건강 문제 중심으로 보았으며, 요통의 주요한 인자로 보고 있으며 risk가 2.7배 증가하며 (p=0.0202), 근육통(어깨, 팔, 목 등)에서는 risk가 1.4배 증가하는 등으로 건강에 직접적인 영향을 주고 있다. 결론은 우리나라의 청소년 근로환경이 계층의 차별성과 다양한 불만이 이루어 질 수가 있는 근로환경의 조건의 삶이 질의 변화가 필요 할 것이다.